2002
DOI: 10.2337/diabetes.51.8.2619
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Metabolic, Vascular, and Nerve Conduction Interrelationships in Experimental Diabetic Neuropathy by Cyclooxygenase Inhibition and Acetyl-l-Carnitine Administration

Abstract: Alterations in cyclooxygenase (COX) pathway activity have been implicated in the pathogenesis of experimental diabetic neuropathy (EDN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 85 publications
(103 reference statements)
6
66
1
1
Order By: Relevance
“…We postulated that upregulation of COX-2, by inflammatory stimuli (12,13), protein kinase C activation (14), and/or oxidative stress (15), contributes to an altered prostaglandin (PG) profile in diabetes that favors vasoconstriction and additional ROS generation, further exacerbating oxidative stress (16). We have also shown that short-term selective chemical COX-2 inhibition in rats and COX-2 gene inactivation in mice prevented diabetes-induced functional and biochemical peripheral nerve deficits (11,16).…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…We postulated that upregulation of COX-2, by inflammatory stimuli (12,13), protein kinase C activation (14), and/or oxidative stress (15), contributes to an altered prostaglandin (PG) profile in diabetes that favors vasoconstriction and additional ROS generation, further exacerbating oxidative stress (16). We have also shown that short-term selective chemical COX-2 inhibition in rats and COX-2 gene inactivation in mice prevented diabetes-induced functional and biochemical peripheral nerve deficits (11,16).…”
mentioning
confidence: 81%
“…Male Wistar rats (200 -250 g) were purchased from Charles River (Wilmington, MA). After fasting overnight, rats were rendered diabetic by STZ as previously described (11). Experimental groups comprised of nondiabetic and diabetic rats (eight or more per group) were randomly assigned to either no treatment or treatment with the selective COX-2 inhibitor (IC50 4.8 nmol/l) celecoxib (50 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 in drinking water) and maintained for up to 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…nuclear factor-kappa B, activator protein-1, signal transducer and activator of transcription-1, octamer-1 and p53 protein via direct binding, poly(ADPribosyl)ation or both [8,9]. This, in turn, up-regulates numerous genes [9,10], including those implicated in the pathogenesis of peripheral diabetic neuropathy (PDN), such as endothelin-1 [11], cyclooxygenase-2 [12,13] and inflammatory genes [14]. Thus, PARP activation can be a trigger of multiple mechanisms implicated in diabetes-associated neuropathic changes.…”
mentioning
confidence: 99%